Wide-range dimmable LED lighting based on QL-SEPIC converter. Issue 1 (2nd January 2019) - Liao, Chien-Nen; Chiu, Huang-Jen; Hsieh, Yao-Ching
ABSTRACT: This paper proposes quadratic-like single-ended primary inductance converter (SEPIC) converter, a DC/DC converter suitable for wide-input voltage range. This circuit can be gated at higher duty ratio compared with conventional SEPIC converter, while the voltage conversion ratio is low. This feature is beneficial for high-input voltage because it prevents the controller from falling into extremely low duty ratio limitation. A prototype circuit is implemented with Pulse-Width-Modulation (PWM) control to drive the Light emitting diode (LED) strings for demonstration of the circuit application. Recent studies have advocated LEDs as efficient and durable technology for lighting applications. A stabilized output converter is required to regulate the current flowing through the LED lamp. The dimming control of the LED light output is implemented by the controller. This converter can be powered from either a 24-Vdc battery or from the universal AC input voltage (up to 360 Vdc ). Such a wide-input voltage application can be found in emergency lighting in which the light is possibly powered either from battery or AC input voltages. Experimental results prove the feasibility of the circuit topology and theoretical analysis.